2007
DOI: 10.1116/1.2737440
|View full text |Cite
|
Sign up to set email alerts
|

Position measurement method for alignment in UV imprint using a high index mold and “electronic” moiré technique

Abstract: In UV imprint, positioning errors can occur between a mold and a wafer due to pressure when there is a contact with the UV resin. The moiré technique, which is produced by superimposition of two gratings, is a well-known and simple method for high-resolution position measurement. However, the authors believe that a direct observation of two separate gratings is more appropriate for higher positioning accuracy. Here they propose a new method for the position measurement, which obtains "electronic" moiré fringes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Therefore, when mold recesses are filled with a UV-curable liquid, mold alignment marks are hardly detected by optical microscopy owing to refractive index matching. To avoid the issue, an effective way is the deposition of an optically functional layer of a light-shielding metal 14) and a high-refractive-index material 16,17) selectively on a silica mold surface. Suzuki et al demonstrated the imprint alignment method by optical microscopy using two cross-shaped concave alignment marks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, when mold recesses are filled with a UV-curable liquid, mold alignment marks are hardly detected by optical microscopy owing to refractive index matching. To avoid the issue, an effective way is the deposition of an optically functional layer of a light-shielding metal 14) and a high-refractive-index material 16,17) selectively on a silica mold surface. Suzuki et al demonstrated the imprint alignment method by optical microscopy using two cross-shaped concave alignment marks.…”
Section: Introductionmentioning
confidence: 99%
“…Precise alignment with multiplicative-type moiré fringes has been widely adopted in proximity lithography, [18][19][20] Xray lithography, 21) and nanoimprint lithography. 14,17,[22][23][24][25][26][27] This arises from the reason because a moiré fringe generating from two gratings with slightly different pitches enables the magnification of a small placement error. Figures 1(a ( )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the issue of refractive index matching, Suehira et al reported the position measurement method for alignment in UV nanoimprinting using a highrefractive index mold and electronic moiré technique. 17) In the literature, they use a silica mold with a 50 nm thick layer of silicon nitride showing a refractive index of 2.0 which is deposited on a silica surface by chemical vapor deposition. However, additional processes of chemical vapor deposition and dry etching of silicon nitride are essential, and the increase in process step leads to an increase in the fabrication cost of imprint molds.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that the refractive index of silica is almost consistent with that of a UV-curable liquid. Therefore, additional alignment marks of a metal light-shielding [14][15][16] or inorganic high-refractiveindex layer 17,18) are essential for optical detection. Other lithographic processes are necessary for the fabrication of additional alignment marks, which increase the cost of mold fabrication reflected in the cost of nanodevices.…”
Section: Introductionmentioning
confidence: 99%